Few Herbivore Species Consume Dominant Macroalgae on a Caribbean Coral Reef - Dell, Claire L. A.; Longo, Guilherme O.; Burkepile, Deron E.; Manfrino, Carrie (Frontiers in Marine Science, 2020)
Coral reefs have changed radically in the last few decades with reefs in the Caribbean now averaging 13% coral cover and 40% macroalgal cover (mostly Dictyota and Lobophora). So, it is time we re-evaluate which species are key to the process of herbivory in these new conditions. The role herbivorous fishes play in controlling macroalgae is often considered by managers and researchers at a guild or family level, but greater resolution is needed to understand the impact of herbivores more fully. We performed feeding assays and behavioural observations of fish feeding to quantify the removal of the most common macroalgae by different herbivorous fish species. In total, we ran 34 hour-long trials using Dictyota and Lobophora across two sites and conducted over 34 hours of observation of 105 fish from eight species in the Cayman Islands, Caribbean. We show that many nominal herbivores did not consume macroalgae but instead targeted the epibionts on macroalgae and other substrates. In fact, only three fish taxa consumed macroalgae as a significant proportion of their feeding: one species of surgeonfish (Acanthurus coeruleus), one species of parrotfish (Sparisoma aurofrenatum), and the third, the chubs (Kyphosus spp.), is a group of species which is not consistently considered as part of the herbivore community in the Caribbean. From our observations, an individual A. coeruleus can consume 44 grams of Dictyota per day, while S. aurofrenatum can consume 50 grams and Kyphosus spp. can consume 100 grams. These values are significantly more than all other herbivorous fish species and suggest these three taxa are key macroalgal consumers in the Caribbean. These results highlight that disentangling the role of individual herbivore species is necessary for critical species to be identified and protected. Furthermore, as reef conditions change, we need to re-evaluate the key functions and species to be more effective at protecting and managing these important ecosystems. With far higher macroalgal coverage than in the past, the few browsing species that remove macroalgae may be increasingly important in promoting reef health.